2009
DOI: 10.4314/tjs.v32i1.18432
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of metacercariae of <i>Diplostomum</i> and <i>Tylodelphys</i> species (diplostomidae) in <i>Clarias</i> species (clariidae) fishes from Lake Victoria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…A number of empirical studies have reported age-infection curves, which either show a continual increase in parasite load with asymptote or a convex dynamics (Quinnell et al, 1992;Krasnov et al, 2006;Musiba, Nkwengulila, 2006;Fergusson et al, 2011). Th e accumulation of metacercariae with the age of a host is a typical occurrence (Wilson et al, 2002) that frequently has been attributed to a long life span of digeneans in intermediate hosts (Musiba, Nkwengulila, 2006;Faltýnková et al, 2011). Continuous exposure of the fi sh to the reinfection throughout the life, their inability to develop age related immunity, and longevity of metacercariae could be an explanation of the increase in the worm load.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A number of empirical studies have reported age-infection curves, which either show a continual increase in parasite load with asymptote or a convex dynamics (Quinnell et al, 1992;Krasnov et al, 2006;Musiba, Nkwengulila, 2006;Fergusson et al, 2011). Th e accumulation of metacercariae with the age of a host is a typical occurrence (Wilson et al, 2002) that frequently has been attributed to a long life span of digeneans in intermediate hosts (Musiba, Nkwengulila, 2006;Faltýnková et al, 2011). Continuous exposure of the fi sh to the reinfection throughout the life, their inability to develop age related immunity, and longevity of metacercariae could be an explanation of the increase in the worm load.…”
Section: Discussionmentioning
confidence: 94%
“…Th ere are a number of mechanisms that might account for such age dynamics of the parasite load. Th ese include parasite-induced host mortality, host-induced parasite mortality, acquired immunity and behavioural changes in older fi sh (Rousset et al, 1996;Wilson et al, 2002;Musiba, Nkwengulila, 2006;Stanko et al, 2006). Both the frequency analysis of parasite distribution and the age dynamics of the parasite aggregation indicate the parasite-induced host mortality occurring in the host-parasite system of T. imbutiforme and L. haematocheilus.…”
Section: Discussionmentioning
confidence: 95%
“…The metacercariae of T. mashonense are commonly encountered in African freshwater systems, utilizing the catfish C. gariepinus as their second intermediate hosts (Mwita and Nkwengulila 2004;Musiba and Nkwengulila 2006;Barson et al 2008;Chibwana and Nkwengulila 2010), but their first intermediate snail hosts were not known, making the present study the first to identify Bulinus spp. (Gastropoda, Planorbidae) as the natural first intermediate host.…”
Section: Discussionmentioning
confidence: 98%
“…Tylodelphys species have a cosmopolitan distribution in freshwater systems, but the most frequently encountered stages are the metacercariae that lodge unencysted in the cranial cavities, brains, and eyes of freshwater fishes (Quaggiotto and Valverde 1992;Flores 1997;Musiba and Nkwengulila 2006;Chibwana and Nkwengulila 2010;Otachi et al 2015) or in the pericardial cavity of some amphibians (King and Van As 1997). Fingerlings in particular may experience high rates of mass mortalities when heavily infected with diplostomid metacercariae or as a result of massive cercarial penetration (Chappell et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In other words most studies have been dealing with occurrences. Diplostomum metacercariae have been reported in the cranial cavity[13,14,46,47], eyes[29,48] and abdominal cavities [21]. Although other Diplostomum species recorded by some studies occur in unusual sites in fi sh host or unusual host, they are neither accompanied with morphometrics nor fi gures.…”
mentioning
confidence: 99%